USE OF THE ‘CAKE - LEARN ENGLISH’ APPLICATION IN TEACHING SPEAKING SKILLS TO SENIOR HIGH SCHOOL STUDENTS - Arrasyid, Muhammad Luqman; Ithriyah, Siti (LPPM UM Metro, 2025)
In the midst of the ongoing Industrial Revolution 4.0, students are increasingly surrounded by rapid technological advancements. Instead of focusing solely on rote memorization, educators are encouraged to design engaging and effective teaching strategies that incorporate technology as a learning tool. Consequently, it is crucial for modern educators particularly English teachers to seamlessly integrate suitable digital media into their classroom practices to support meaningful and enjoyable teaching and learning outcomes. This research investigates the implementation of the Cake application as a tool for enhancing high school students’ speaking abilities and examines their perceptions of the platform. Employing a mixed methods approach, combining both quantitative and qualitative data. The quantitative data were gathered through pre- and post-questionnaires with Likert-scale items, while qualitative data were obtained from open-ended questions to explore students’ perceptions and experiences. The participants consisted of students from class XI Social I at SMAN 19 Bekasi. The findings reveal that the Cake application proved to be an effective medium for supporting speaking skill development, increasing student engagement, and fostering self-confidence in English language learning. Keyword: cake application, teaching tool, speaking skill